Recollections of the Catawba Valley - Boger, Gordon (Appalachian State University, 1983)
Published in 1983, Recollections of the Catawba Valley is a selection of family stories, local history, and mountain folklore chosen by Alexander Mull and Gordon Boger who were longtime citizens of the valley in North Carolina. The Mull family was one of the earliest settlers in the region, and Boger, although born elsewhere, was considered a native of the valley. Some of the stories in this volume were originally published in The News Herald of Morganton, as both authors were longtime contributors to the paper. W. H. Plemmons, second President of Appalachian State University, wrote the foreward.